Associations between job demands, job resources and patient-related burnout among physicians: results from a multicentre observational study - Joost van den Berg; Renée Scheepers; Milou Silkens; Kiki Lombarts (BMJ Open)
Objectives To investigate associations of job demands and resources with patient-related burnout among physicians.Design Multicentre observational study.Setting Fifty medical departments at 14 (academic and non-academic) hospitals in the Netherlands.Participants Four hundred sixty-five physicians (71.6% response rate), comprising 385 (82.8%) medical specialists and 80 (17.2%) residents.Main outcome measures Job demands (workload and bureaucratic demands), job resources (participation in decision making, development opportunities, leader’s inspiration, relationships with colleagues and patients)—measured with the validated Questionnaire of Experience and Evaluation of Work and Physician Worklife Survey—and patient-related burnout, measured using the validated Copenhagen Burnout Inventory.Results Patient-related burnout was positively associated with workload (b=0.36; 95% CI, 0.25 to 0.48; p<0.001) and negatively associated with development opportunities (b=–0.18; 95% CI, –0.27 to –0.08; p<0.001) and relationships with patients (b=–0.12; 95% CI, –0.22 to –0.03; p=0.01). Relationships with patients moderated the association between bureaucratic demands and patient-related burnout (b=–0.15; 95% CI, –0.27 to –0.04; p=0.01).Conclusions Physicians with high workloads and few development opportunities reported higher levels of patient-related burnout. Those with positive patient relationships were less likely to experience patient-related burnout, even in the presence of excessive bureaucracy. Therefore, positive physician–patient relationships may be supported to reduce the likelihood of physicians’ patient-related burnout. However, the specific support needed to effectively reduce patient-related burnout may vary per healthcare context and thus requires intensified research across healthcare systems and settings.